Ways of disseminating of Chinese language (Journal of Oriental Studies, 2018)
In a developed society, China and Kazakhstan establish a close relationship.In this regard, wishing to learn Chinese language with each passingyear more and more. This article discusses the strategic friendly relationsbetween Kazakhstan and China.